2020
DOI: 10.1093/intimm/dxaa060
|View full text |Cite
|
Sign up to set email alerts
|

Bim establishes the B-cell repertoire from early to late in the immune response

Abstract: In T cell-dependent antibody responses, some of the activated B cells differentiate along extrafollicular pathways into low-affinity memory and plasma cells, whereas others are involved in subsequent GC formation in follicular pathways, in which somatic hypermutation and affinity maturation occur. The present study demonstrated that Bim, a proapoptotic BH3-only member of the Bcl-2 family, contributes to the establishment of the B cell repertoire from early to late stages of immune responses to T-cell dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
0
2
Order By: Relevance
“…Finally, there was a 42-fold higher PC than MCB production. Studies have shown the number of PCs and MBCs generated spleen and bone marrow during an immune response (Kishi et al, 2010;Weisel et al, 2016;Sugimoto-Ishige et al, 2020). Nevertheless, these numbers represent percentages of observed PCs and MBCs from the total number of splenic or bone marrow cells, which are not translatable to the number of output cells from a single GC and therefore are not directly comparable with our results.…”
Section: Resultscontrasting
confidence: 80%
“…Finally, there was a 42-fold higher PC than MCB production. Studies have shown the number of PCs and MBCs generated spleen and bone marrow during an immune response (Kishi et al, 2010;Weisel et al, 2016;Sugimoto-Ishige et al, 2020). Nevertheless, these numbers represent percentages of observed PCs and MBCs from the total number of splenic or bone marrow cells, which are not translatable to the number of output cells from a single GC and therefore are not directly comparable with our results.…”
Section: Resultscontrasting
confidence: 80%
“…Finally, there was a 42-fold higher PC than MCB production. Studies have shown the number of PCs and MBCs generated spleen and bone marrow during an immune response (Kishi et al, 2010;Weisel et al, 2016;Sugimoto-Ishige et al, 2020). Nevertheless, these numbers represent percentages of observed PCs and MBCs from the total number of splenic or bone marrow cells, which are not translatable to the number of output cells from a single GC and therefore are not directly comparable with our results.…”
Section: Resultscontrasting
confidence: 80%